Relation of central and brachial blood pressure to left ventricular hypertrophy. The Czech Post-MONICA Study - Wohlfahrt, P; Wichterle, D; Seidlerová, J; Filipovský, J; Bruthans, J; Adámková, V; Cífková, R (Journal of human hypertension, 2012)
Central blood pressure (BP) has been shown to be a better predictor of target organ damage and cardiovascular events than brachial BP. Whether central BP is a better predictor of left ventricular hypertrophy (LVH) determined by electrocardiography (ECG) is not known. Radial applanation tonometry and ECG were performed in 728 subjects from the Czech Post-MONICA Study (a randomly selected 1% population sample). LVH was determined using the Sokolow-Lyon index and Cornell product; central pressure was derived from radial pulse. Of 657 subjects included in the analysis, 17 (9.4%) below 45 years and 43 (9%) over 45 years had LVH. In multiple linear regression analysis, the Sokolow-Lyon index in younger individuals was only associated with male sex and low BMI, with no association with BP found. In older individuals, LVH was associated with higher central and brachial BP. In separate binary logistic regression analyses adjusted for covariates, the odds ratio for central systolic pressure was higher than those for brachial systolic and pulse pressure in LVH prediction. Noninvasively determined central pressure in subjects over 45 years is more strongly related to ECG LVH than brachial pressure. This further supports a closer association of central pressure with target organ damage. Voltage criteria of LVH are not independently associated with central or brachial BP in younger individuals.
Keywords: Sex Factors; Humans; index tělesné hmotnosti; Body Mass Index; Hypertension; prevalence; Female; dospělí; Hypertrophy, Left Ventricular; hypertrofie levé komory srdeční; lidé; sexuální faktory; Adult; ženské pohlaví; krevní tlak; Male; hypertenze; Czech Republic; Prevalence; Česká republika; mužské pohlaví; Blood Pressure